افسانوں کے اردو تراجم میں معنویت: ایک فنی تجزیہ: (THE MEANING IN THE URDU TRANSLATIONS OF SHORT STORIES: A CRITICAL ANALYSIS) - ڈاکٹر اسد محمود خان (Policy Research Journal, 2025)
The proposed study aims to explore the nuances and complexities involved in translating short stories into Urdu. By critically analyzing selected Urdu translations of short fiction, the research investigates how meaning is conveyed, adapted, and sometimes altered in the process of translation. The study delves into the challenges faced by translators, including cultural context, idiomatic expressions, and literary style, and how these elements influence the essence of the original work. Additionally, the research examines the role of translation in expanding the reach of global literary traditions within the Urdu-speaking community, emphasizing both the limitations and possibilities inherent in cross-cultural literary exchanges. Through a comprehensive textual analysis, this study seeks to shed light on the dynamics of translation as a medium for interpreting meaning, preserving cultural values, and fostering a deeper understanding of world literature within the context of Urdu.